Lasers speed up board production. - Ehsani, A.R.
A technology for writing conductor patterns directly on photoresist simplifies the manufacture of printed-circuit boards and also multiplies yields. If a laser beam is switched on and off as it scans, it can be made to trace a pattern on a light-sensitive material directly, without intervening steps. There is no need to prepare a photonegative, or phototool, to block light from background regions, as is done at present in "printing" circuit boards. The laser can scan conductors directly on photoresist covering an embryonic copper-clad nonconductive circuit board; subsequent board processing remains conventional-developing the resist, exposing and etching part of the copper surface, and removing the rest of the resist. In this way, the up-and-coming laser direct imaging (LDI) systems eliminate the need for a phototool and thereby slash production time of circuit board prototypes by at least one half. So far, several manufacturers of prototypes and medium volumes of printed-circuit boards (about 100 m2 per day) have adopted LDI. In contrast with older technologies, LDI can produce even large panels (up to 750 mm by 600 mm) with fine features (conductor lines and spaces, for example) at high yields
Keywords: Circuit board production; Conductor lines; Conductor patterns writing; Embryonic copper-clad nonconductive circuit board; Laser beam switching; Laser direct imaging systems; Light-sensitive material; Photoresist; Printed-circuit boards manufacture; Production time reduction